CFD modeling of a road tunnel with multiple sources of Co. case of study: boqueron-I tunnel - Blanco, Armando J.; Rojas-Solorzano, L.; Urbina, Rafael J. (Research Gate, 2009)
This work aims to the modeling of CO transport in one section considered critical of the Boqueron I tunnel, located on the outskirts of Caracas, the capital city of Venezuela, with a scenario where vehicles are stopped by an interruption of traffic. This scenario considers a relationship between the number of large-sized vehicles (buses or trucks) and small-sized vehicles (passenger cars) reported by transit statistics and also, it considers the semi-transverse ventilation system in the tunnel. It is explored the influence of the ventilation on the flow patterns and its relationship to the regions with the highest CO concentration. The finite-volume based finite element method is used for the discretization of the computational domain and the integration of the governing equations. The transient 3D-incompressible Navier-Stokes, energy, mass and species conservation equations, along with the k-e turbulence equations, were discretized, using higher-order numerical schemes in space. The numerical simulation is performed using a fully implicit coupled treatment of the set of resulting discrete transport equations
Keywords: Research Subject Categories::TECHNOLOGY::Engineering mechanics; mechanical engineering